THERMAL DYNAMICS OF BRAKE DEVICES - Vozniy, Andriy; Vudvud, Oleksandr (Problems of Friction and Wear, 2025)
Theoretical and experimental studies of brake friction pairs under bench conditions under load in different fields of frictional interaction, accompanied by variable operating parameters, made it possible to obtain the following. Show that the main parameter in thermal dynamics is the dynamic coefficient of friction, which is a complex operational parameter of most calculated dependencies with its fluctuating properties. Set the factors that can be set, and a number of factors are classified as difficult to control, and therefore for calculations it is necessary to operate with the values of the intervals of their change, from which to use the average values. To illustrate the dimensionless regularities of changes in sliding speed, braking torque and friction power for different types of brake friction pairs, and for the latter dimensional parameters from the braking time for a disc-pad brake for a vehicle in laboratory conditions. To evaluate the regularity of changes in the dynamic coefficient of the assembly "FK-24 - steel 35KHNL" during frictional interaction under the influence of mechanical, electrical, thermal and chemical fields.